2016
DOI: 10.1021/acsnano.6b01544
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchically Structured Fullerene C70 Cube for Sensing Volatile Aromatic Solvent Vapors

Abstract: We report the preparation of hierarchically structured fullerene C70 cubes (HFC) composed of mesoporous C70 nanorods with crystalline pore walls. Highly crystalline cubic shape C70 crystals (FC) were grown at a liquid-liquid interface formed between tert-butyl alcohol and C70 solution in mesitylene. HFCs were then prepared by washing with isopropanol of the FC at 25 °C. The growth directions and diameters of C70 nanorods could be controlled by varying washing conditions. HFCs perform as an excellent sensing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 60 publications
0
93
0
Order By: Relevance
“…Similarly, formation of cubic structures from C 70 alone and hierarchically‐structured fullerene C 70 cubes with sensing antenna has been demonstrated (Figure ) . Highly crystalline cubic‐shape C 70 crystals were first grown at a liquid‐liquid interface formed between tert ‐butyl alcohol and C 70 solution in mesitylene using an ultrasound‐assisted method.…”
Section: Nanoarchitectonics With Fullerene Familiesmentioning
confidence: 85%
“…Similarly, formation of cubic structures from C 70 alone and hierarchically‐structured fullerene C 70 cubes with sensing antenna has been demonstrated (Figure ) . Highly crystalline cubic‐shape C 70 crystals were first grown at a liquid‐liquid interface formed between tert ‐butyl alcohol and C 70 solution in mesitylene using an ultrasound‐assisted method.…”
Section: Nanoarchitectonics With Fullerene Familiesmentioning
confidence: 85%
“…Some have been used as sensing materials in QCM devices . Recently, hierarchically structured cubes, microcube structures with many small antenna rods, were successfully fabricated through the liquid–liquid interfacial precipitation of C 70 and post‐solvent treatment (Figure ) . As an analogy to insects with sensitive antennae, QCM electrodes with antenna‐decorated C 70 cubes showed more sensitive responses to aromatic solvent vapors, such as toluene and pyridine, than those with antenna‐free C 70 cubes.…”
Section: Materials Nanoarchitectonics With Qcmmentioning
confidence: 99%
“…Fullerene cubes of C 70 composition with hierarchically structures consisting of mesoporous C 70 nano-size rods having crystalline walls have been prepared. [24] Microscopy studies have shown that cubic crystals are formed as a result of growth at a liquid liquid interfacial zone. Both tertiary butyl alcohol and mesitylene were used here.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%